Pendampingan Pemetaan Masalah Praktik Akuntansi Yayasan - Arthik Davianti; Steffi Kartika; Dyah Ayu Ningrum; Nurul Rizki Anindita; Rizvanya Anugra Arighi; Mahesa Deni Dwi Permana; Wiwit Damayanti; Nurul Ummi (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
The Community Service activity was conducted as an effort to improve the application of accounting in non-profit organizations. This activity was important considering that there are various important aspects in the accounting recording process that have not generally been implemented in non-profit organizations. Yayasan Hati Beriman Salatiga, as a non-profit organization engaged in several fields and has implemented the accounting recording process using Zahir application. The implementation of the community service was carried out by data collection through interviews and observation of zahir application application. The Community Service Team found that the internal controls in the implementation of the accounting recording process had not been implemented. Therefore, the Team suggested recommendations for the separation of functions in the accounting recording process by utilizing the resources owned and optimizing the use of recording applications.